Is Ultrasonic Bone Scalpel Useful in Le Fort I Osteotomy? - DEMİRBAŞ, AHMET EMİN; BİLGE, SUHEYB; ÇELEBİ, SELİN; KÜTÜK, Nükhet; KÜTÜK, NÜKHET; ALKAN, Alper; ALKAN, ALPER (My University, 2020)
Purpose: Safety and precision are 2 main goals in research to improve bone cutting in maxillofacial surgery. The aim of this prospective clinical study was to analyze the outcomes using an ultrasonic bone scalpel versus a piezoelectric surgical device and the conventional technique in a Le Fort I osteotomy.